Pico Della Mirandola: o esoterismo como categoria filosófica - Casoretti, Anna Maria (2020)
The main intention of the Renaissance philosopher Pico della Mirandola was to conciliate different doctrines and systems, guided by the perception of the existence of metaphysical conceptions capable of integration in their highest degrees. The passion for the proof of correspondences leads him to a path of reconciling with the past and the consequent construction of correlation strategies whose key principle lies in the idea that concepts concerning the highest levels of reality penetrate reciprocally. His project of teleological convergence contemplates elements derived from the most diverse perspectives, whether philosophical, theological or mysteriological. The presence of traditions that have perpetuated themselves around forms of esoteric transmission, such as Greek mysteriology, Jewish Kabbalah and Egyptian Hermeticism, is found in the midst of such perspectives, as well as some records of philosophical content and manifestations of primitive Christianity that have employed specific forms of language related to secrecy. The aim of this investigation is to point out such elements and show that their repetition allows us to characterize the set as a category present in Pico’s thought, used not only as a rhetorical resource, but as a possibility of expansion and synthesis of interpretative possibilities. De Hominis Dignitate, Conclusiones Nongentae and Heptaplus are adopted as sources of investigation